Individual and combined antiparasitic effect of six plant metabolites against Leishmania amazonensis and Trypanosoma cruzi. Issue 7 (1st April 2016) - Sandjo, Louis P.; de Moraes, Milene H.; Kuete, Victor; Kamdoum, Blaise C.; Ngadjui, Bonaventure T.; Steindel, Mario
Graphical abstract: Abstract: Six plant metabolites including isobavachalcone (1 ), 4-hydroxylonchocarpine (2 ), and ( E )-1-(2, 2-dimethyl-2 H -chromen-6-yl)-3-(4-hydroxyphenyl)prop-2-en-1-one (3 ), 6, 8-(di-3-methyl-but-2-enyl)eriodictyol (4 ), damnacanthal (5 ), and buesgenine (6 ) were evaluated for their leishmanicidal and trypanocidal activities against intracellular amastigotes of Leishmania amazonensis and Trypanosoma cruzi . Compounds2 –4 and6 displayed antileishmanial activity while3 and5 showed trypanocidal effect. The leishmanicidal activity of6 was expressed with the lowest IC50 (5.70 μg/mL) whereas the most trypanocidal metabolite (5 ) showed its activity with IC50 at 11.14 μg/mL. In addition, antiprotozoal effect of mixtures of1 –6 prepared at different ratios (3:1, 1:1, and 1:3) was also investigated. Interestingly, 1 and2 initially inactive against T. cruzi, displayed trypanocidal activities when mixed together. This activity increased when3 (13.63 μg/mL) was combined with1 in ratios 1:1 (10.01 μg/mL) and 3:1 (7.78 μg/mL). Moreover, the leishmanicidal effect of4 against L. amazonensis increased in the mixture6 /4 (1:3).